Międzywojenne artykuły gimnazjalistek z Kaszub i Krakowa = Interwar articles Middle school students from Kashubia and Krakow - Linkner, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
We are here about articles by students from interwar midlle schools from Koscierzyna and Kraków. The articles have various topies. This allows you to get to know the thoughts of the students during this time.
Keywords: Hel; Gdańsk; Kościerzyna; międzywojenne gimnazjum; interwar gymnasium